Mitochondrial DNA-based diversity study of Hungarian brown hares (Lepus europaeus Pallas 1778) - Soós, Noémi; Kusza, Szilvia (Acta Agraria Debreceniensis, 2016)
The brown hare being an important game species which is widespread across the European continent has been in focus of many population genetic studies. However only a few comprising researches can be found on the diversity of Central-European populations. The aim of our large scale long term ongoing study is to fill this gap of information on the species by describing the genetic history and structure of the brown hare populations of the area using both mitochondrial DNA markers and genomic skin and hair colour regulating genes. This article gives forth a part of our results concerning the mitochondrial DNA diversity of Hungarian brown hares based on amplification of a 512 bp long D-loop sequence. N=39 tissue or hair samples have been collected from 15 sampling sites on the Hungarian Great Plain. We have described a high level of haplotype diversity (Hd=0.879±0.044) based on a 410 bp alignment of our sequences. We have found 17 haplotypes within our sample set with the nucleotid diversity of π=0.01167±0.0022. Our ongoing research shows high genetic diversity for the brown hare in the studied region and a second alignment with 156 sequences downloaded from GenBank indicates a geographic pattern of haplotypes among the studied populations though these results need confirmation by our further analyses.